Analysis of the Meaning of the Word Haram in the Quran: A Semantic Study by Toshihiko Izutsu - Khurinin, Aisy Najiha; Nugroho, Kharis (Universitas Muhammadiyah Surakarta, 2023)
This article explains the meaning of the word haram in the Quran. So far, the word haram is known as a legal term in Islam. However, it turns out that when the word haram is placed in different editorials, it has a different meaning. Using a semantic approach developed by Toshihiko Izutsu, the author examines the fundamental meaning and relational meaning of the word haram using syntagmatic and paradigmatic analysis and then examines the meaning and usage of the word haram in the pre-Quran, Quranic, and post-Quranic periods, which then reveals how the worldview is viewed regarding the meaning of the word haram.